Efficient N-arylation of azole compounds utilizing selective aryl-transfer TMP-iodonium(III) reagents. Issue 18 (2nd May 2019) - Koseki, Daichi; Aoto, Erika; Shoji, Toshitaka; Watanabe, Kazuma; In, Yasuko; Kita, Yasuyuki; Dohi, Toshifumi
Graphical abstract: Highlights: Efficient aryl amination of azole compounds. Coupling reaction employing reactive pseudo -halide. TMP-iodonium(III) for reactive/selective aryl-transfer. Abstract: It was determined that diaryliodonium(III) triflates bearing a trimethoxybenzene (TMP) auxiliary are more reactive than the reported selective aryl-transfer iodonium salts in the N -arylation of benzimidazoles and other types of azole compounds under catalytic conditions. The TMP-iodonium(III) salts can thus effectively facilitate the reaction at 50 °C or below, producing the corresponding N -arylated biaryls without the formation of TMP-derived coupling byproducts. Utilization of this TMP reagent under mild conditions would prevent the underlying problem of participation of the auxiliary group in the coupling reactions, which is observed while using the iodonium(III) salts that require elevated temperatures.